(untitled) (Research, Society and Development, 2021)
The organizational routines reveal themselves as an important mechanism in the orgnizational dynamics. Their study has been through diferent visions over time, since were initially perceived as simple mechanisms of stability and reliability, starting to be seen as inductive instruments of innovation and change. This evolution of understanding still occurs and it’s necessary to know how the organizational routines studies may contribute to the organizational develpment. This particular study has the purpose to present a bibliometric analysis about organizational routines, characterizing the most recent panorama about the subject matter. Scientific articles about organizational routines were surveyed at Scielo, Scopus and Web of Science databases in the period from 2015 to 2019, then analysed and labeled by journals, countries of origin, keywords, number of citations, associated themes and study types. The results points out that the most recent studies share the modern view that the organizational routines are an organizational dynamics element, which allows the process of change. The bibliometric analysis, besides of exhibit a reliable and replicable method to analyse a particular field of study, has identified a scarcity of research on this matter in Brazil, showing a gap between the scientific knowledge produced nationally and abroad. The research has also indicated several associated themes like routines dynamics, innovation, change, learning, dynamic capabilities and stability, allowing the managers to apply new approaches to the organizational routines in theirs organizations.